2015
DOI: 10.1016/j.yrtph.2015.05.018
|View full text |Cite
|
Sign up to set email alerts
|

An approach to ingredient screening and toxicological risk assessment of flavours in e-liquids

Abstract: Flavour ingredients are an essential part of e-liquids. Their responsible selection and inclusion levels in e-liquids must be guided by toxicological principles. We propose an approach to the screening and toxicological risk assessment of flavour ingredients for e-liquids. The screening involves purity requirements and avoiding ingredients that are carcinogenic, mutagenic or toxic to reproduction. Additionally, owing to the uncertainties involved in potency determination and the derivation of a tolerable level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 38 publications
0
45
0
Order By: Relevance
“…In addition to nicotine, ECIG aerosol can contain other toxicants, some of which are created by the thermal breakdown of the liquid ingredients. [26][27][28][29] These harmful constituents include glycols, aldehydes, metals, volatile organic compounds (VOCs), and polycyclic aromatic hydrocarbons (PAHs). 30 Glyoxal and methyl glyoxal (di-aldehydes) have also been found in the ECIG aerosol; these compounds do not appear in cigarette smoke.…”
Section: Ecigs and Their Design Featuresmentioning
confidence: 99%
“…In addition to nicotine, ECIG aerosol can contain other toxicants, some of which are created by the thermal breakdown of the liquid ingredients. [26][27][28][29] These harmful constituents include glycols, aldehydes, metals, volatile organic compounds (VOCs), and polycyclic aromatic hydrocarbons (PAHs). 30 Glyoxal and methyl glyoxal (di-aldehydes) have also been found in the ECIG aerosol; these compounds do not appear in cigarette smoke.…”
Section: Ecigs and Their Design Featuresmentioning
confidence: 99%
“…An earlier proposal promoted the selection of e-liquid ingredients with certain purity criteria and to avoid ingredients known to be carcinogenic, mutagenic, and reprotoxic (Costigan and Meredith 2015). The authors also suggested the exclusion of known respiratory sensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…From a manufacturing point of view, innovation in product design combined with rigorous product stewardship should be in place and actively enforced during the development of ecigarettes in order to minimize potential hazards and risks from the products. 54 Product manufacturing quality is also critical in ensuring consistency and stability during the full life cycle of Chemical Research in Toxicology pubs.acs.org/crt Article the product, helping to reduce variability across time for consumers and regulatory testing alike.…”
Section: Discussionmentioning
confidence: 99%